An electronic synaptic device based on HfO2TiOx bilayer structure memristor with self-compliance and deep-RESET characteristics. (10th August 2018) - Liu, Jian; Yang, Huafeng; Ji, Yang; Ma, Zhongyuan; Chen, Kunji; Zhang, Xinxin; Zhang, Hui; Sun, Yang; Huang, Xinfan; Oda, Shunri
Abstract: We reported on a Ti/HfO2 /TiOx /Pt memristor with self-compliance, deep-RESET characteristics and excellent switching performance, including ultrafast program/erase speed (10 ns), a large memory window (10 3 ) and good pulse endurance (10 7 cycles). The self-compliance and deep-RESET characteristics are beneficial for protecting the device from permanent breakdown in both SET and RESET processes especially under the pulse operation mode. In addition to bistable state switching, we also achieved multiple or even continuous conductance state switching under a DC sweep and a pulse-train operation mode in the Ti/HfO2 /TiOx /Pt memristor, which can be seen as a substitution of a biological synapse. The capability of continuous modulation conductance (synaptic weight) in the Ti/HfO2 /TiOx /Pt memristor was investigated and the potentiation and depression characteristics of the synaptic weight could be precisely tuned by the number or amplitude of the input pulse-train. Moreover, clear experimental evidence of short-term plasticity (STP) and long-term plasticity (LTP) in a single memristor was also demonstrated. Increasing the pulse amplitude or width, or decreasing the interval of two adjacent pulses of the input pulse-train resulted in the memristor behavior transitioning from STP to LTP. The realization of those important synaptic functions in the Ti/HfO2 /TiOx /Pt memristor may be suitable for applications in artificial neural systems.